THE IMPACT OF HUMAN DISPLACEMENT ON THE ATTAINMENT OF SDG 4 IN NIGERIA - Musa, Muhammad Nurudden; Sa’idu, Isa (African Journal of Social and Behavioural Sciences, 2025)
The phenomenon of human displacement resulting in the production of internally displaced persons (IDPs) and refugees has been a recurring issue in Nigeria in recent times. It affects all human engagement, most importantly the attainment of sustainable development goal number four as it pertains to access and provision of education for the vulnerable, like the displaced people who are scattered by conflicts in different locations in Nigeria. The study utilizes secondary materials to depict how human displacements and the sporadic movements of the victims pose a challenge to the actualization of the educational goal of the sustainable development programme. The paper found that violent disruption of human settlements hinders provision and access to education among the displaced persons, thereby impeding access to education as envisioned in the Sustainable Development Goal under focus, which is anchored on widening access to quality education among the vulnerable groups. The paper is significant in that it attempts to explore the discourse on the centrality of a tranquil human settlement towards the sustenance of provision and access to education among the internally displaced in Nigeria.